Predicting overall survival and resection in patients with locally advanced pancreatic cancer treated with FOLFIRINOX: Development and internal validation of two nomograms. Issue 4 (11th June 2021) - Brada, Lilly J. H.; Walma, Marieke S.; Daamen, Lois A.; van Roessel, Stijn; van Dam, Ronald M.; de Hingh, Ignace H.; Liem, Mike L. S.; de Meijer, Vincent E.; Patijn, Gijs A.; Festen, Sebastiaan; Stommel, Martijn W. J.; Bosscha, Koop; et al.
Abstract: Background and Objectives: Patients with locally advanced pancreatic cancer (LAPC) are increasingly treated with FOLFIRINOX, resulting in improved survival and resection of tumors that were initially unresectable. It remains unclear, however, which specific patients benefit from FOLFIRINOX. Two nomograms were developed predicting overall survival (OS) and resection at the start of FOLFIRINOX for LAPC. Methods: From our multicenter, prospective LAPC registry in 14 Dutch hospitals, LAPC patients starting first‐line FOLFIRINOX (April 2015–December 2017) were included. Stepwise backward selection according to the Akaike Information Criterion was used to identify independent baseline predictors for OS and resection. Two prognostic nomograms were generated. Results: A total of 252 patients were included, with a median OS of 14 months. Thirty‐two patients (13%) underwent resection, with a median OS of 23 months. Older age, female sex, Charlson Comorbidity Index ≤1, and CA 19.9 < 274 were independent factors predicting a better OS (c‐index: 0.61). WHO ps >1, involvement of the superior mesenteric artery, celiac trunk, and superior mesenteric vein ≥ 270° were independent factors decreasing the probability of resection (c‐index: 0.79). Conclusions: Two nomograms were developed to predict OS and resection in patients with LAPC before starting treatment with FOLFIRINOX. These nomograms could be beneficial in the shared decision‐making process and counseling of these patients.